2017
DOI: 10.1089/mdr.2015.0318
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Antimicrobial Resistance in Escherichia coli in Pigs Receiving Oral Antimicrobial Treatment: A Systematic Review

Abstract: The aim of this literature review was to identify risk factors in addition to antimicrobial treatment for antimicrobial resistance (AMR) occurrence in commensal Escherichia coli in pigs. A variety of studies were searched in 2014 and 2015. Studies identified as potentially relevant were assessed against eligibility criteria such as observation or experiment (no review), presentation of risk factors in addition to (single dosage) antimicrobial use, risk factors for but not resulting from AMR, and the same antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
4
32
0
1
Order By: Relevance
“…A literature systematic review based on thirteen relevant articles revealed a relationship between AMR pattern in herds and dosage, route of administration and frequency of AMU. Several additional factors had a statistically significant influence on AMR on herd level, as space allowance, cleanliness, time span between sampling and treatment and distance to another farm [48]. Higher odds ratios were found for resistance of E. coli to quinolones, aminoglycosides and tetracycline in herds with oral administration of antimicrobials [7].…”
Section: Discussionmentioning
confidence: 99%
“…A literature systematic review based on thirteen relevant articles revealed a relationship between AMR pattern in herds and dosage, route of administration and frequency of AMU. Several additional factors had a statistically significant influence on AMR on herd level, as space allowance, cleanliness, time span between sampling and treatment and distance to another farm [48]. Higher odds ratios were found for resistance of E. coli to quinolones, aminoglycosides and tetracycline in herds with oral administration of antimicrobials [7].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that a rising probability of infection with an increased number of animals could be responsible for this and refer to Österberg et al [ 22 ], Hautekiet et al [ 23 ] und García-Feliz et al [ 24 ]. Regarding the link between herd size and antimicrobial resistance, various patterns are also described [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the factors listed above, that for the most part relate only to genetic mechanisms, there are many others that may affect the emergence and spread of AMR and the probability of transfer of AMR bacteria or the determinants therein from animals to humans. Such factors include dosage, including underdosage (Kohanski et al., ; van der Horst et al., ; Callens et al., ; Pardon et al., ), dosing regimens, including volume of use (Chantziaras et al., ), administration route (Burow and Käsbohrer, ) and animal husbandry conditions (Catry et al., ). There are many pathways through which resistance can be transmitted between animals, humans and the environment (Landers et al., ).…”
Section: Introductionmentioning
confidence: 99%